Benzocaine loaded biodegradable poly-(D,L-lactide-co-glycolide) nanocapsules: factorial design and characterization - Moraes, Carolina Morales; de Matos, Angelica Prado; de Paula, Eneida; Rosa, Andre Henrique [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Elsevier B.V., 2009)
Local anesthetics are able to induce pain relief since they bind to the sodium channel of excitable membranes, blocking the influx of sodium ions and the propagation of the nervous impulse. Benzocaine (BZC) is a local anesthetic that presents limited application in topical formulations due to its low water-solubility. This study aimed to develop polymeric nanocapsules as a drug delivery system for the local anesthetic benzocaine (BZC). To do so, BZC loaded poly(D,L-lactide-co-glycolide) (PLGA) nanocapsules were prepared using the nanoprecipitation method and were characterized. The factorial experimental design was used to study the influence of four different independent variables oil response to nanocapsules drug loading. The physical characteristics of PLGA nanocapsules were evaluated by analyzing the particle size, the polydispersion index and the zeta potential, using a particle size analyzer. The results of the optimized formulation showed a size distribution with a polydispersity index of 0.12. an average diameter of 123 nm, zeta potential of -33.6 mV and a drug loading of more than 69%. The release profiles showed a significant difference in the release behavior for the pure drug in solution when compared with that containing benzocaine loaded PLGA nanocapsules. Thus, the prepared nonocapsules described here may be of clinical importance in both the processes of stabilization and delivery of benzocaine for pain treatment. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Benzocaine; Nanocapsules; PLGA; Drug delivery